PENGARUH KEAKTIFAN KOMITE AUDIT DAN KEBERADAAN AUDITOR EKSTERNAL BIG FOUR TERHADAP MANAJEMEN LABA - Fadhykarastika Ananda Putri; Dul Muid (Diponegoro Journal of Accounting, 2014)
This study aims to examine impact of activeness of the audit committee, the Big Four existence, and the combination between activeness of the audit committee and the Big Four existence on earnings management, in manufacturing company for period of 2010-2012, which are registered on the Indonesian Stock Exchange.            This study using secondary data from annual report and financial report. Research variable being used earnings management (DACC), activeness of the audit committee (FM), the Big Four existence (BF), and the combination between activeness of the audit committee and the Big Four existence (FM_BF). First by performs ordinary least square regression analysis to find the discretionary accrual (DACC). Subsequently performed descriptive statistics, correlation, and ordinary least square regression analysis to test each hypothesis.            The results of this study indicate that the activeness of the audit committee can decrease earnings management but not significantly, meanwhile the Big Four existence in firm can decrease earnings management significantly. However, the combination effect between activeness of the audit committee and the Big Four existence indicate potential increase in earnings management but not significantly.